Giant foliate fibroadenoma (cystosarcoma phyllodes) - del Campo, Alberto; Crespo, Luis; Falconi, Luis (Cirugía del Uruguay, 2020)
Five ,cases of giant fibroadenoma of the breast are reported. Their outstanding characteristics are: unilat,erality, development in ·two times, important size with preserved movility and cutaneous alterations, which ·may produce ulceration. Radiological and anatomo pathological characteristics and diagnosis are analyzed. The difficult dignosis among bening ( the nost frequent ones) and maling formations are emphasized. The best procedure will be therefore, simple mastectomy.